Analisis Rasio Likuiditas Terhadap Nilai Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Kharisma Aulia Insani; Nur Amalina (Jurnal Ilmu Ekonomi, Manajemen dan Bisnis, 2023)
The aim of this study is to determine the effect of the current ratio, quick ratio, and cash ratio on firm value. The data used in this study is secondary data in the form of financial statements of manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2022. The sampling technique used in this research is purposive sampling. Multiple linear regression analysis was used as the analytical method. The results showed that the current ratio has a positive effect on firm value, the quick ratio has a negative effect on firm value, and the cash ratio has a positive effect on firm value